Market power analysis in Mongolian wheat industry - Purev, Erdenebat; Byamba, Purev (Applied Studies in Agribusiness and Commerce, 2020)
Mongolia has been in transition from a planned economy to a market economy for more than 20 years. In many sectors of the economy, it is necessary to define which market mechanisms exist. Grain occupies important economic sector in Mongolian economy. The current state of the wheat market has been studied based on NEIO research methods. In this study, the data for years from 2000 to 2017 and from 2007 to 2017 about wheat and wheat seed sector were taken through 6 indicators. We estimated the supply and demand functions for wheat and wheat seed. Using these functions, we defined market behavior, cost function, price elasticities, and market equilibrium. The capacity setting for product prices of wheat producers is weak, and this market is likely free-style competition.